2015
DOI: 10.1039/c5cy00211g
|View full text |Cite
|
Sign up to set email alerts
|

Catalytic dehydrofluorination of 1,1,1,2-tetrafluoroethane to synthesize trifluoroethylene over a modified NiO/Al2O3 catalyst

Abstract: The close linear relationship between Lewis acid sites and catalytic activity for the dehydrofluorination of CF3CFH2.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
18
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 37 publications
(19 citation statements)
references
References 30 publications
1
18
0
Order By: Relevance
“…The results of NH 3 TPD and CO 2 TPD (Figure and Table S2) also reveal that the fluorinated MgO exhibits weaker acidity/basicity than MgO, but its amounts of acid/base sites are bigger than those of MgO. Furthermore, the pyridine IR spectra (Figure S4) confirm the existence of many Lewis acid sites on the fluorinated MgO, shown by the vibration bands at 1446 and 1606 cm −1 , whereas the MgO possesses very few Lewis acid sites. Wojciechowska et al .…”
Section: Resultsmentioning
confidence: 72%
See 1 more Smart Citation
“…The results of NH 3 TPD and CO 2 TPD (Figure and Table S2) also reveal that the fluorinated MgO exhibits weaker acidity/basicity than MgO, but its amounts of acid/base sites are bigger than those of MgO. Furthermore, the pyridine IR spectra (Figure S4) confirm the existence of many Lewis acid sites on the fluorinated MgO, shown by the vibration bands at 1446 and 1606 cm −1 , whereas the MgO possesses very few Lewis acid sites. Wojciechowska et al .…”
Section: Resultsmentioning
confidence: 72%
“…Nevertheless, as seen in the conversion of HCFC‐244bb, the fluorinated MgO displayed the highest selectivity for dehydrofluorination among the tested catalyst, whereas MgO displayed high dehydrochlorination selectivity. Several groups have reported that surface Lewis acid sites are related with the dehydrofluorination process . Consequently, the Lewis acid sites of the catalyst play a key role for dehydrofluorination of HCFC‐244bb.…”
Section: Resultsmentioning
confidence: 99%
“…The metal modification on catalysts is an effective method to improve the catalytic performance including the aim product selectivity . The AC−H catalysts were modified by impregnation of K and used to catalytic pyrolysis of HCFC‐142 to synthesize VDF at 600 °C.…”
Section: Resultsmentioning
confidence: 99%
“…A facile sol‐gel synthesis of nano α‐AlF 3 , which can improve the thermostability of AlF 3 , and show highly active catalyst for dehydrofluorination of hydrofluorocarbons due to the large Lewis acidic amounts . Han et al reported the combustion synthesis for amorphous Al and Cr composite, and as a stable catalyst for dehydrofluorination of 1, 1‐difluoroethane during 60 h, the interaction between Cr species and Al species provides relatively high amount of defect and is favorable for the formation active species. Wang et al prepared the supported Pd/AlF 3 catalyst and found that the addition of Pd significantly improved the stability of AlF 3 catalyst due to Pd additive could effectively pyrolyse carbon deposit .…”
Section: Introductionmentioning
confidence: 99%